Influence of sinker timing on loop shape, width and areal density of weft-knitted cotton plain jersey fabric. - Mohammad Hossain; Akm Mobarok Hossain; Md Abdullah Al Mamun; Aiead Ibne Fahim; Nowshin Nigar Rafa; Emtiaz Ahmed Pappu; Abu Darda; Shafin Arafat; Syed Tohedul Islam (PLoS ONE)
This study aims to explore the influence of sinker timing-a relative positional setting of two primary knitting elements, i.e., needle and sinker, on some important knitted fabric parameters and related properties. Plain jersey fabric samples were produced from cotton yarn (linear density of 19.68 Tex) at three different quality values (loop lengths of 2.77 mm, 2.84 mm, and 2.90 mm respectively) on a positive feed-based multi-feeder circular knitting machine. Three different sinker timings (regular, forwarding, and retracting) were used for each quality setting; thus, a total of 9 (nine) fabric samples were developed for experimental purposes. It was found that forward sinker timing resulted in an increase in the loop shape factor concerning regular sinker timing and vice versa. However, stitch densities were almost the same for all settings of sinker timing at a particular value of loop length. Consequently, fabric width was highest for forward timing and fabric areal density remained almost unchanged. Also visual inspection revealed no noticeable differences among the fabric samples.